Traditional Knowledge Management (TKM) through Biosprospecting: Mainstreaming Scientific Research Trends and Techniques for Inclusive and Sustainable Education - Alvin Romualdo; Jinnifer Arroyo; Eden Grace Suriaga; Rose Fuentes (East Asian Journal of Multidisciplinary Research, 2022)
Traditional knowledge management (TKM) or indigenous knowledge management (IKM) is essential in preserving traditional knowledge through resource and biodiversity management along with bioprospecting putative medicinal plants deemed to have medicinal uses and benefits for knowledge literacy and product development. This study was documented to determine the significance of seminar-workshops on scientific researches in preserving and updating traditional knowledge through bioprospecting thus, strengthening traditional knowledge. Forty-four (44) STEM students and three (3) Science teachers from Mamasapano National High School participated in the seminar-workshop on scientific research trends and techniques. Post evaluation test was administered to assess the response of the students vis-à-vis the significance of seminar-workshops in strengthening traditional knowledge through bioprospecting. Results revealed that all students strongly agreed that the conduct of seminar-workshops is essential in safeguarding traditional knowledge which is nowadays at stake due to modernization. Results further implied the need to conduct more seminar-workshops across the region especially in the indigenous and local communities to preserve the traditional knowledge and to foster inclusive and sustainable education.